2019
DOI: 10.1177/0300060519893234
|View full text |Cite
|
Sign up to set email alerts
|

Trends in chronic hepatitis B treatment-related research from 1973 to 2018: a bibliometric and visual analysis

Abstract: Objective Chronic hepatitis B (CHB) is a worldwide disease and the most common cause of liver cancer. This study aimed to identify specific areas of research activity concerning CHB treatment between 1973 and 2018 and to aid in identifying new areas for future development. Methods The literature was searched from the GoPubMed and Web of Science databases using terms related to CHB treatment, analyzed with bibliometric methods and visualized using VOSviewer. Results A total of 9486 and 5883 papers were collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…In this study, the most important journals in the field of HDV were determined to be the Journal of Hepatology (n = 123 articles, 8.04%); Hepatology (n = 121 articles, 7.91%); and the Journal of Medical Virology (n = 50 articles, 3.27%). In a bibliometric analysis of chronic hepatitis B treatment-related research, it has been shown that the Journal of Hepatology, Hepatology, and Chinese Journal of Hepatology have the highest number of articles published [30]. In a bibliometric analysis of HAV, the most attractive journals were Vaccine, Hepatology, and the Journal of Medical Virology [31].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the most important journals in the field of HDV were determined to be the Journal of Hepatology (n = 123 articles, 8.04%); Hepatology (n = 121 articles, 7.91%); and the Journal of Medical Virology (n = 50 articles, 3.27%). In a bibliometric analysis of chronic hepatitis B treatment-related research, it has been shown that the Journal of Hepatology, Hepatology, and Chinese Journal of Hepatology have the highest number of articles published [30]. In a bibliometric analysis of HAV, the most attractive journals were Vaccine, Hepatology, and the Journal of Medical Virology [31].…”
Section: Discussionmentioning
confidence: 99%
“…All data were extracted on a single day in April 2019 as WoS is an open database which is regularly updated with new publications. The use of a single source bibliometric database was conducted due to its comprehensive indexing of journals, suitability and extensive use for similar analyses in the literature (20,(22)(23)(24).…”
Section: Bibliometric Data and Search Strategymentioning
confidence: 99%
“…Hence, it is important to conduct systematic, comprehensive, and scientific analyses to specify the effect of these publications, confirm the hotspots, and identify possible promising fields in this area. Bibliometric and visual analysis can generate network maps based on the co-occurrence of keywords, authors, and topics ( 8 , 9 ), thereby offering scientific production and development situations in this field ( 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%